Lymph node co-infection of Mycobacterium avium complex and cytomegalovirus in an acquired immunodeficiency syndrome patient - Arya Hedjazi; Marzieh Hosseini; Amin Hoseinzadeh (MDPI AG, 2013)
Acquired immunodeficiency syndrome patients are known to have an increased tendency for developing opportunistic infections. However, there are no reports of simultaneous lymph node involvement of cytomegalovirus and Mycobacterium avium complex in a human immunodeficiency virus-positive patient. We report a 31-year-old man who presented with acute abdominal pain and tenderness and weight loss. He died a few hours after admission. Autopsy studies showed coinfection of cytomegalovirus, Mycobacterium avium complex and human immunodeficiency virus. Our case emphasizes the need to be careful in evaluating opportunistic infections in severely immunodepressed acquired immunodeficiency syndrome patients. This case report is the first manifestation of acquired immunodeficiency syndrome in this patient.